2008
DOI: 10.1097/01.prs.0000299386.73127.a7
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Alloplastic Materials in Rhinoplasty Surgery: A Meta-Analysis

Abstract: Alloplastic implants in rhinoplastic surgery have acceptable complication rates and can be used when autogenous materials are unavailable or insufficient. Outcomes with Medpor or Gore-Tex implants may be slightly better than those with silicone. Improved reporting of implant failures and follow-up times in future studies are needed to better define specific guidelines for the use of these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 53 publications
2
97
1
9
Order By: Relevance
“…53,60 The possible complications, with potential rates of occurrence and when they may be expected to occur, should be discussed prior to surgery. 73 Rhee et al found that the distribution of the overall complications included intranasal synechiae (14%), infection (9%), graft resorption (7%), and residual septal deviation (7%). 60 Other reported complications included failure to improve nasal airway patency, residual external deformity, hematoma, graft dislocation/migration, septal perforation, vestibulitis, and tissue reaction to alloplastic materials, as well as the lack of subjective improvement of the underlying condition.…”
Section: Supporting Textmentioning
confidence: 99%
“…53,60 The possible complications, with potential rates of occurrence and when they may be expected to occur, should be discussed prior to surgery. 73 Rhee et al found that the distribution of the overall complications included intranasal synechiae (14%), infection (9%), graft resorption (7%), and residual septal deviation (7%). 60 Other reported complications included failure to improve nasal airway patency, residual external deformity, hematoma, graft dislocation/migration, septal perforation, vestibulitis, and tissue reaction to alloplastic materials, as well as the lack of subjective improvement of the underlying condition.…”
Section: Supporting Textmentioning
confidence: 99%
“…It is known to be non-antigenic, non-allergenic, and can be carved to various shapes [6]. However, some studies suggest that using Medpor for nasal augmentation is not recommended because of its variable and unpredictable resorption rate [7,8]. In our experience, Medpor is difficult to remove during revision rhinoplasties.…”
Section: Graft Materialsmentioning
confidence: 75%
“…[3] and extrusion rates, ranging from 3.1% [4] to as high as 21% [5] and often require removal, which can be extremely difficult because of tissue incorporation. [5,6] Explantation surgery is treacherous as there is a high incidence of button holing, thinning, and irregularity of overlying skin and damage to surrounding structures.…”
Section: These Implants Have High Infection (3-4%)mentioning
confidence: 99%